Rethinking the assumptions of intervention research concerned with care at home for people with dementia - Symonds-Brown, Holly; Ceci, Christine; Judge, Harkeert (My University, 2018)
Aging populations have been positioned as a challenge to health and social service planning around the world, a situation even more pronounced in the case of persons with a diagnosis of dementia. While policy responses emphasize that care be provided for persons with dementia in home settings for as long as possible and that family carers be supported in the provision of this care, finding good ways to support families as they do the work of ‘delaying institutionalization’ has been challenging despite decades of intervention research intended to develop and evaluate interventions to support families. In this context of limited effectiveness it is useful to examine the assumptions informing research practices. Problematization is a method of literature analysis useful for clarifying and challenging assumptions informing a field of research in order to generate new approaches to research or new research questions. Our analysis suggests that although community-based intervention research has contributed significant knowledge about the kinds of things that might help families, there are limitations related to the dominant assumptions underlying the field. We highlight three areas for re-consideration: the overriding focus on caregiver–care recipient dyads, the under-determination of the object(s) of inquiry and the algorithmic nature of interventions themselves. Issues in these areas, we argue, arise from a commitment to homogeneity characteristic of biomedical models of disease that may need to be rethought in the face of consequential heterogeneity among research populations. That is, there is a mismatch between ‘dementia’ in the intervention research literature and ‘dementia’ in the life that is consequential for families living with these concerns.
Keywords: dementia; family caregiving; intervention research; care at home; problematization